CATALYTIC DIMERIZATION OF OLEIC ACID OVER HIERARCHICAL ZSM-5 - (NIM:10512078), FAUZI
Dimeric fatty acids are intermediates such as polybasic acid in synthesizing in polyester and poly amide. Dimeric fatty acids can be produced from oleic acid through the dimerization of oleic acid catalyzed by ZSM-5. However, the catalytic reaction of ZSM-5 has a problem in the deactivation of the catalyst so that mesoporous pore needs that increases the diffusion rate of product. In this research, characterize synthetic and catalytic reactivity test on dimerization of oleic acid at atmospheric pressure and temperature 255oC with variation of time 6 hours, 12 hours and 18 hours. Zeolite characterize by XRD, SEM, and fisisoption. XRD results indicate that ZSM-5 zeolite has a crystalline structure. The Si / Al ratio analysis shows that commercial zeolites have Si / A SEM result indicatethat ZSM-5 synthetic has spherical-like morphology. The product of dimerization of oleic acid was analyzed using Thin Layer Chromatography (TLC), Nuclear Magnetic Resonance (NMR). TLC result observations indicate that product has a smaller Rf at t = 18 hours with a commercial zeolite who indicating the rate of product diffusion is low and polarity of the product is more polar than the oleic acid. From NMR, the product compared to oleic acid obtained a higher (H sp2 and H sp3) ratio and at C-NMR obtained a specific dimeric peak at chemical shift of 25.615.